2008
DOI: 10.1021/es801636v
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Biomarkers and Mechanisms of Copper-Induced Olfactory Injury in Zebrafish

Abstract: Metals such as copper disrupt olfactory function in fish. Unfortunately, little is understood of the molecular consequences of copper olfactory impairment, thus hindering the development of relevant diagnostic tools of olfactory injury. To address this critical data gap, we analyzed gene expression within olfactory tissues of adult zebrafish exposed to CuCl2 (6, 16, 40 ppb) for 24 hrs. Transcriptional markers of copper impairment within the entire olfactory system were identified and specific genes of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 45 publications
12
63
1
Order By: Relevance
“…The results from this study do not completely agree with the findings of Tilton et al (2008) who reported on the effect of copper at the transcriptional level. Tilton et al reported a substantial difference in the transcription of genes in pooled olfactory tissues of zebrafish, including, olfactory rosettes, telencephalon, and the underlying olfactory bulb.…”
Section: Figcontrasting
confidence: 99%
See 1 more Smart Citation
“…The results from this study do not completely agree with the findings of Tilton et al (2008) who reported on the effect of copper at the transcriptional level. Tilton et al reported a substantial difference in the transcription of genes in pooled olfactory tissues of zebrafish, including, olfactory rosettes, telencephalon, and the underlying olfactory bulb.…”
Section: Figcontrasting
confidence: 99%
“…Tilton et al (2008Tilton et al ( , 2011),) exposed zebrafish (Danio rerio) to low concentrations of copper and/or chlorpyrifos. Tilton et al (2008) exposed zebrafish to increasing concentrations of copper (6.3, 16, and 40 g/L) for 24 h and found that the transcription of many genes was altered in response to copper exposure, with the largest number of genes having altered transcription at the highest tested concentrations. Tilton et al (2011) exposed zebrafish to copper and/or chlorpyrifos (an organophosphate pesticide) for 24 h and both contaminants showed unique transcriptional signatures.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, olfactory tissue contains molecular receptors, ion channels, transporters, and gene expression different from those of the ionoregulatory tissue [17,18,29]. However, from a coarse modeling perspective, the geochemical basis of the BLM appears to be flexible enough to predict olfactory-related responses relatively well in a variety of water chemistries, even though the BLM does not explicitly include information about metal-induced processes occurring on or in olfactory tissue, just as it predicts lethality relatively well, even though it does not explicitly include information about metal-induced processes occurring on or in ionoregulatory tissue.…”
Section: Biotic Ligand Model-based Cu Criteria Are Protectivementioning
confidence: 99%
“…Copper can also interact with the olfactory system of fish and aquatic invertebrates [2][3][4][5][6][7][8][9], causing them to avoid Cu-containing water while their olfactory system is not impaired and to lose important functions such as attraction to food odors and reproductive pheromones, or avoidance of predators, when olfaction is impaired [9][10][11][12][13][14][15][16]. At relatively low Cu concentrations that do not kill olfactory neurons, olfactory impairment in fish is caused by depression of a variety of crucial genes within the olfactory signal transduction pathway and elsewhere in olfactory tissues [17], and, at higher Cu concentrations that kill olfactory neurons, olfactory signals cannot be stimulated and transduced to the brain [4,16]. Recent studies have demonstrated avoidance of Cu or impairment of olfaction in salmonid fishes exposed to concentrations as low as approximately 1 to 2 mg Cu/L (lake whitefish, Coregonus clupeaformis [10]; Chinook salmon, Oncorhynchus tshawytscha, and rainbow trout, Oncorhynchus mykiss [11]; coho salmon, Oncorhynchus kisutch [5,15,18,19]), prompting public concern that important activities such as spawning and predator avoidance might be impaired in Cu-contaminated streams in the Pacific Northwest of the United States [ [20,21]; see http://oregonstate.edu/ua/ncs/ archives/2007/mar/osunoaa-study-copper-autos-other-sourcesincreases-predation-risk-salmon].…”
Section: Introductionmentioning
confidence: 99%
“…Some substances, which cause neurotoxic effects on ORNs [24,25], have been shown to alter the OE protein-signaling pathway. In zebrafish, copper toxicity [26], causes a negative effect on calcium channels, ion transport, and G protein-coupled olfactory receptors. This could be a possible explanation for ORNs death in the OE and the subsequent decrease in OMP labeling.…”
Section: Discussionmentioning
confidence: 99%